A Comparative Study on Preference Towards Intraday & Long-Term Investment in Stock Market Among Gen-Z in Ahmedabad City - Purohit, Vraj; Shah, Kunj; Vidani, Jignesh (MultiTech Publisher, 2024)
This study elaborates on the investment preference of Gen Z in Ahmedabad in terms of the comparative inclination towards intraday trading and long-term investing in the stock market. The research discovers key factors that influence these preferences: Their perception of the potential to build wealth, confidence in the decision-making process, an understanding of risk tolerance, and the role of technology as well as social media. A structured hypothesis-testing approach revealed that the investment preference is, in fact very long-term, a perception of stability and more effective wealth accumulation rather than the high-risk, high-reward nature of intraday trading. Confidence in making informed decisions, especially in intraday trading,